REVITALISASI PELAKSANAAN KEGIATAN JURU PEMANTAU JENTIK DI ERA PANDEMI COVID-19 DI KAMPUNG PELITA MEDIKA I KAMPUNG PELITA MEDIKA 1 DI KELURAHAN MERANTI PANDAK KOTA PEKANBARU - Fifia Chandra; Handayani Handayani; Rita Endriani; Andri Mahadi; Pivi Yordani Eka P; Riska Norlaili; Afandi Ahmad; Rizki bunaya (Riau Journal of Empowerment, 2022)
Pelita Medika 1 Village Meranti Pandak Village is an endemic area for dengue hemorrhagic fever (DHF). This is supported by environmental conditions and community behavior that is at risk for the occurrence of DHF. Therefore, since 2018 in the area, larval monitoring activities have been carried out. Since 2019 it has stopped until now. Therefore, it is necessary to revitalize the implementation of the larva monitoring activities, especially in the current era of the COVID-19 pandemic. Where the purpose of this revitalization is to refresh the knowledge and skills of jumantik cadres in the implementation of larva monitoring and motivate these cadres to commit to carrying out these activities regularly. This activity is carried out through counseling, training, demonstration, and role play methods. The learning media used are using power points for presentations, video playback of larva monitoring activities. This activity resulted in an increase in the knowledge and skills of the jumantik cadres in carrying out larva monitoring, as well as a declaration of commitment to reactivate larva monitoring activities with the 1 house 1 jumantik program.